THE EFFECTIVENESS OF THE COMPETITIVE IMPLEMENTATION OF ARCHERY IN THE PREPARATORY PERIOD - Tarasova, L.V.; Shilin, Yu.N.; Tarasov, P.Yu.; Gombozhapova, H-T. D. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of athletes' sports implementation at the beginning of the preparatory period. Methods and structure of the study. The work is based on the study and analysis of the protocols of competitive performances of archers at the Russian winter championship. Mathematical methods for calculating the obtained data were used: calculation of Student's t-test and coefficient of variation. Results and conclusions. The work performed indicates the heterogeneity of the technical readiness of the top three leaders of the Russian championship. It is noted that the average results of the top three leaders of the first round are lower than the average results of the leaders of the second round of the qualifying round, which indicates a different level of special preparedness of athletes, both in men and women. Passing the second round of the qualifying round requires the manifestation of special endurance, which indicates the need to maintain it among the leaders of the first round. On the contrary, insufficient implementation in the first round of the leaders of the second round indicates an insufficient level of “training”, which requires a longer warm-up before entering the start of the qualifying round.